In situ Polymerized FDU‐12/Poly(methyl methacrylate) and FDU‐12/polyamide 6 Nanocomposites for Cd2+ Adsorption. Issue 3 (12th January 2021) - Zabihi, Samyar; Jamshidian, Sahar; Soltani, Roozbeh; Pelalak, Rasool; Heidari, Zahra; Marjani, Azam; Ghadiri, Mahdi
Abstract: Large‐pore mesoporous silica FDU‐12 was synthesized and functionalized with silane coupling agents bearing methacrylate and diamino groups. Diamino‐functionalized FDU‐12/polyamide 6 and methacrylate‐functionalized FDU‐12/poly(methyl methacrylate) nanocomposites were prepared via in situ polymerization approach. These two synthesized nanocomposites were used as potential adsorbents for the removal of Cd 2+ cations from aqueous media. The impact of different adsorption factors affecting the adsorption process was investigated, and isotherm and kinetic studies were conducted to gain a better understanding of adsorption mechanisms involved in the removal process of Cd 2+ by the adsorbents. Experimental and computational results demonstrated that the adsorbents have acceptable performance for Cd 2+ uptake. Abstract : Two nanocomposites of functionalized large‐pore FDU‐12 mesoporous silica/ polymer nanocomposites were synthesized. Methyl methacrylate and caprolactam monomers were in situ polymerized inside the mesopores of FDU‐12 to form poly(methyl methacrylate) and polyimide 6 chains grafted on the surface of FDU‐12. These nanocomposites were applied as potential adsorbents for Cd 2+ adsorption from water.